Keterlaksanaan Layanan Bimbingan TIK terhadap Guru dalam Proses Belajar Mengajar di UPT SMP Negeri 1 Alla Kabupaten Enrekang - Jumaring Jumaring (CV. Syntax Corporation Indonesia, 2022)
The development of computer technology and learning media requires teachers to provide new innovations in the delivery of teaching materials. However, not all teachers are good at operating computer technology and developing learning media. Therefore, there is a need for ICT teachers to provide ICT mentoring services for subject teachers so that they can keep up with existing technological developments. The purpose of the study was to determine the results of implementing ICT assistance services for teachers in the teaching and learning process at UPT SMP Negeri 1 Alla, Enricon Regency. Data collection methods used are observation and questionnaires. The samples of this study were UN subject teachers, namely 5 mathematics teachers, 5 Indonesian language teachers, 4 English teachers, and 4 comprehensive science teachers, a total of 18 teachers. The data analysis technique used is descriptive percentage analysis and expert validation. UPT SMP Negeri 1 Alla, Enrekang Regency. Research findings on the application of teacher ICT assistance services in the teaching and learning process are generally very high. This can be seen from the very high scale in the development of learning resources, development of learning media, reporting of learning processes and learning outcomes. Higher scores are also achieved in preparation for studies and study assessment. Information and communication technology teachers must be implemented properly to guide teachers in the teaching and learning process, so that the use of computer technology-assisted tools can be utilized optimally.